KEDUDUKAN TEORI ILMU MANAJEMEN DAN MENGANALISIS TEORI MANAJEMEN PENDIDIKAN - Utami, Maharani Windu; Romadhon, Abdul Malik; Hasan, Adzar Ladja Amil; Fauzi, Anis; Hidayat, Wahyu (Jurnal Manajemen Pendidikan, 2024)
Management has theories that are classified into seven kinds of groups, namely: classical management theory, behavioral management theory, scientific management theory, system analysis management theory, results-based management theory, and quality management theory, and classical organizational management theory. This study aims to examine the position of management science theory in the context of education. The research method used in this article is qualitative research with a literature study approach. Research with qualitative methods is a method that obtains descriptive data results in the form of words and sentences in writing sourced from the data and information being studied. In-depth analysis will be carried out on management theories relevant to the world of education. This research is expected to provide a more comprehensive understanding of how general management concepts can be applied and adapted in the context of educational institutions. Thus, this research is expected to contribute to the development of more effective and efficient educational management practices.